Methodological challenges in utilizing miRNAs as circulating biomarkers. Issue 3 (18th February 2014) - Moldovan, Leni; Batte, Kara E.; Trgovcich, Joanne; Wisler, Jon; Marsh, Clay B.; Piper, Melissa
Abstract MicroRNAs (miRNAs) have emerged as important regulators in the post‐transcriptional control of gene expression. The discovery of their presence not only in tissues but also in extratissular fluids, including blood, urine and cerebro‐spinal fluid, together with their changes in expression in various pathological conditions, has implicated these extracellular miRNAs as informative biomarkers of disease. However, exploiting miRNAs in this capacity requires methodological rigour. Here, we report several key procedural aspects of miRNA isolation from plasma and serum, as exemplified by research in cardiovascular and pulmonary diseases. We also highlight the advantages and disadvantages of various profiling methods to determine the expression levels of plasma‐ and serum‐derived miRNAs. Attention to such methodological details is critical, as circulating miRNAs become diagnostic tools for various human diseases.